Method for catalytically synthesizing two-dimensional diamond under normal pressure and application
By mixing Ti3C2 MXene with Ni powder under normal pressure, using chlorine etching and high-stress nickel catalyst to form two-dimensional diamond, the problems of harsh preparation conditions and stable properties of two-dimensional diamonds are solved, and stable synthesis and low-cost processes are achieved.
Patent Information
- Application Number
- CN202411289530.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, the preparation conditions for two-dimensional diamonds are relatively harsh, and under common methods, the two-dimensional diamond will be converted to graphene structure after releasing pressure, or the introduction of non-carbon atoms in chemical induction methods affects its essential properties.
Mix the small layer of Ti3C2 MXene with Ni metal powder under normal pressure, and after pre-pressing and argon protection, a chlorine etching reaction was carried out. A high-stress nickel catalyst was used to form a two-dimensional diamond structure, and heated up in an air atmosphere to remove the non-diamond phase. .
The stable synthesis of two-dimensional diamond under normal pressure is achieved, with the lateral dimensions and thicknesses in the range of 100-180nm and 2.47-4.12nm. The process is simple and the cost is low, and the problem of high pressure and non-carbon atoms is avoided.
Smart Images

Figure CN119118122A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel carbon materials, and in particular relates to a method for catalytically synthesizing two-dimensional diamond under normal pressure. Background Art
[0002] Two-dimensional diamond combines the excellent properties of bulk diamond and two-dimensional materials. It has excellent heat transfer performance, ultra-low friction, high natural frequency and adjustable band gap. It has potential technical and industrial application prospects in nanophotonics, ultra-sensitive resonator sensors and improving wear resistance. However, the preparation conditions of two-dimensional diamond are often harsh. For example, high pressure can transform a few-layer graphene into a two-dimensional diamond structure, but the method of preparing two-dimensional diamond is reversible. Once the pressure is released, the two-dimensional diamond will transform back into a graphene structure. Although chemical induction can transform a few-layer graphene into a stable two-dimensional diamond, the introduction of non-carbon atoms will affect the essential properties of two-dimensional diamond.
[0003] For example, the patent application with publication number CN114959632 A in the prior art discloses a method for preparing a two-dimensional diamond nanosheet material, using graphite having an allotrope with diamond as a diamond confined growth template to prepare a diamond / graphite composite nanosheet, and etching the graphite phase and amorphous carbon phase therein by a post-processing method, so that a large area of diamond nanosheets can be prepared. However, the preparation conditions of the two-dimensional diamond in this method are relatively harsh.
[0004] Therefore, developing a new method to synthesize two-dimensional diamond under normal pressure is a research hotspot in this field. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art and in order to solve the problem of harsh preparation conditions of two-dimensional diamond, the purpose of the present invention is to design and provide a method and application of catalytic synthesis of two-dimensional diamond under normal pressure. The method of the present invention can synthesize stable two-dimensional diamond under normal pressure.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In one aspect, the present invention provides a method for catalytically synthesizing two-dimensional diamond under normal pressure, comprising the following steps:
[0008] (1) Take a few-layer Ti3C2 MXene powder and a Ni metal powder, mix them evenly, and pre-press them into Ti3C2 / Ni cylindrical blocks (to prevent the few-layer Ti3C2 MXene from coming into contact with air and causing oxidation reaction), then apply compaction stress and maintain it to obtain a Ti3C2 / Ni compact;
[0009] (2) The Ti3C2 / Ni compact is placed in a tube furnace, argon is introduced for the first time (to expel the residual air in the quartz tube), the temperature is increased (to avoid oxidation of the few-layer Ti3C2 MXene during the heating process), the argon is turned off and chlorine is introduced for etching reaction, and after the reaction is completed, the chlorine is stopped and argon is introduced at the same time to obtain a carbon material with a two-dimensional diamond structure;
[0010] (3) A carbon material having a two-dimensional diamond structure is placed in a tube furnace, and the temperature is increased and maintained in an air atmosphere to obtain a two-dimensional diamond, so as to remove the non-diamond phase in the sample.
[0011] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the preparation method of the few-layer Ti3C2 MXene in step (1) is:
[0012] (a) Weigh LiF, add it to HCl solution, and stir at room temperature to obtain a uniform mixed solution;
[0013] (b) Ti3AlC2 powder is added to the mixed solution, and the mixture is stirred in a water bath for reaction. After the reaction is completed, the mixture is washed by centrifugation with HCl, and then washed by centrifugation with water several times until the pH value reaches 6-7. The mixture is ultrasonically treated in an ice bath under an inert gas atmosphere (the temperature is kept below 5°C to avoid oxidation of Ti3C2 MXene during the ultrasonic process), and then centrifuged. The upper layer of liquid is taken, frozen, and dried to obtain a few-layer Ti3C2 MXene powder.
[0014] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the mass volume ratio of LiF to HCl solution in step (a) is (3.2-4): (32-48) g / mL;
[0015] The concentration of the HCl solution is 9M;
[0016] The stirring time is 15 to 30 minutes.
[0017] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the mass ratio of the Ti3AlC2 powder to LiF in step (b) is 1:(1.6-2);
[0018] The conditions for water bath stirring are: temperature 40-50°C, time 30-36h;
[0019] The conditions of the HCl centrifugal washing are: a rotation speed of 3200-3800 rpm, a time of 5-10 min, and a centrifugal washing number of 2-3 times;
[0020] The ultrasonic treatment conditions are: ultrasonic power 160-200W, ultrasonic time 2-4h;
[0021] The conditions for the water centrifugal washing are: a rotation speed of 3200 to 3800 rpm and a time of 20 to 30 minutes.
[0022] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the mass ratio of the few-layer Ti3C2 MXene powder to the Ni metal powder in step (1) is 1:1 to 10;
[0023] The number of layers of the Ti3C2 MXene powder is ≤10;
[0024] The particle size of the Ni metal powder is 50nm-1μm;
[0025] The pre-pressing pressure is 2-8 MPa;
[0026] The applied compaction stress is 5 to 6 GPa and maintained for 5 to 10 minutes.
[0027] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the flow rate of the first introduction of argon gas in step (2) is 300 to 600 mL / min, and the time is 10 to 20 min;
[0028] The heating conditions are: heating rate 15°C / min, heating to 1000°C;
[0029] The flow rate of the chlorine gas is 30-60 mL / min;
[0030] The etching reaction time is 1.5 to 2.5 hours.
[0031] In the method for catalytic synthesis of two-dimensional diamond under normal pressure, the heating condition in step (3) is: heating rate 5-10°C / min, heating to 475-525°C;
[0032] The holding time is 15 to 20 hours.
[0033] In a second aspect, the present invention provides application of any of the methods described above in synthesizing two-dimensional diamond.
[0034] In a third aspect, the present invention provides a two-dimensional diamond synthesized by any of the methods described above.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The present invention introduces nano-scale nickel powder into the interlayer of a few-layer Ti3C2 MXene in a high stress state by applying compaction stress through a six-sided top press. In the subsequent chlorine etching process, the Ti atoms in the Ti3C2 MXene are selectively etched away, and the remaining C atoms are reorganized to form a two-dimensional diamond structure under the action of a nickel catalyst in a high stress state. The lateral size range of the two-dimensional diamond prepared by the present invention is 100-180nm, and the thickness range is 2.47-4.12nm. The synthesis conditions of the method of the present invention are easy to achieve, the process is simple, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The transmission photographs of the two-dimensional diamond obtained in Example 1 of the present invention, wherein (a) is a TEM image of the 2D diamond, (b) is an HRTEM image of the area marked by the red box in the middle, (c) is an enlarged HRTEM image of the area marked by the red box in Figure b, and the inset is an FFT image of the corresponding area, (d) is a TEM image of the 2D diamond, (e) is an HRTEM image of the area marked by the red box in Figure d, (f) is an enlarged HRTEM image of the area marked by the red box in Figure e, and the inset is an FFT image of the corresponding area;
[0038] Figure 2 These are AFM images of two-dimensional diamond obtained in Example 1 of the present invention, wherein (a) is the AFM image of the 2D diamond, and (b) is the height curve corresponding to the 2D diamond in Figure a. DETAILED DESCRIPTION
[0039] The technical solution of the present invention will be further described in detail below in conjunction with embodiments and drawings.
[0040] Embodiment 1:
[0041] (1) Preparation of few-layer Ti3C2 MXene: 4.0 g of LiF was slowly added to 40 mL of 9 M HCl solution and stirred at room temperature for 30 min to obtain a uniform mixed solution. Subsequently, 2 g of Ti3AlC2 powder was slowly added to the mixed solution and placed in a 50 ° C water bath and stirred for 30 h. After the reaction, it was first washed and centrifuged with 240 mL of dilute HCl (2M) (3500 rpm, 5 min), and then washed and centrifuged with deionized water for multiple times until the pH value of the solution reached 6-7. Then, it was ultrasonically treated in an ice bath under the protection of inert gas, with an ultrasonic power of 180 W and an ultrasonic time of 2 h. After the ultrasonic reaction was completed, it was subjected to high-speed centrifugation (3500 rpm, 20 min), and the upper layer of liquid was poured into a glass culture dish. After freezing in a refrigerator overnight, it was placed in a freeze dryer and freeze-dried for 12 h to obtain few-layer Ti3C2 MXene powder.
[0042] (2) Preparation of Ti3C2 / Ni compacts: Few-layer Ti3C2 MXene was used as a precursor and nano-sized nickel powder was used as a catalyst in a mass ratio of 0.25 g:1 g. The mixture was evenly mixed in a glove box and loaded into a 9.5 mm diameter cemented carbide mold. The Ti3C2 / Ni cylindrical blocks were pre-pressed using a powder tablet press. Finally, a 6 GPa compaction stress was applied to the Ti3C2 / Ni cylindrical blocks using a six-sided top press and the pressure was maintained for 10 min.
[0043] (3) Chlorine etching of Ti3C2 / Ni compacts: The Ti3C2 / Ni compacts were placed in a tubular furnace, and high-purity argon was introduced at a flow rate of 600 mL / min for 10 min. Then, under the protection of the argon atmosphere, the temperature was raised to 1000°C at a rate of 15°C / min. When the temperature in the furnace reached 1000°C, the argon was turned off and chlorine was introduced for etching reaction. The flow rate of chlorine was 30 mL / min, and the etching reaction time was 2 h. After the reaction was completed, the introduction of chlorine was stopped and high-purity argon was introduced. The compacts were cooled to room temperature under the protection of the inert gas argon to obtain a carbon material with a two-dimensional diamond structure.
[0044] (3) Air oxidation purification treatment of 2D diamond: The carbon material sample with a two-dimensional diamond structure obtained by chlorine etching in step 3 is placed in a tube furnace, and heated to 500°C at a rate of 10°C / min in an air atmosphere and maintained at this temperature for 17 hours to remove the non-diamond phase in the sample.
[0045] The transmission electron microscope observation of the two-dimensional diamond after air oxidation purification showed that Figure 1 shown. Figure 1 TEM images of a and d show a large number of sheet-like stacked 2D diamonds. Figure 1 b is Figure 1 In the HRTEM image of the marked area in a, an irregularly shaped two-dimensional diamond can be observed. Figure 1 c is Figure 1 b A further magnified high-resolution transmission image of the marked area shows that the lattice fringes with a lattice spacing of 0.2060 nm can be clearly seen, corresponding to the (111) crystal plane of cubic diamond. Figure 1 From the FFT results in the illustration c, it can be obtained that the interplanar spacing of the two-dimensional diamond is 0.2060, 0.1780 and 0.1260 nm, which correspond to the interplanar spacing values of the (111), (200) and (220) characteristic crystal planes of cubic diamond, respectively. Figure 1 d is a TEM image of 2D diamond observed under another field of view, which also shows the morphological features of many lamellar structures gathered together. Figure 1 e is Figure 1 d is an HRTEM image of a single 2D diamond. From the image, we can clearly see the morphological features of layered stacking. According to the further enlarged HRTEM image and FFT results of the red box area in the 2D diamond ( Figure 1 f) Lattice fringes with a lattice spacing of 0.2060 nm can be clearly observed, corresponding to the cubic diamond (111) crystal plane. Figure 2 This is a typical AFM image of two-dimensional diamond. From the AFM results, it can be concluded that the lateral size of this two-dimensional diamond is about 150nm and the thickness is about 2.5nm, which has the typical characteristics of two-dimensional materials.
[0046] Embodiment 2:
[0047] (1) Preparation of few-layer Ti3C2 MXene: 3.2 g of LiF was slowly added to 48 mL of 9 M HCl solution and stirred at room temperature for 15 min to obtain a uniform mixed solution. Subsequently, 2 g of Ti3AlC2 powder was slowly added to the mixed solution and placed in a 50 ° C water bath and stirred for 30 h. After the reaction, it was first washed and centrifuged with 200 mL of dilute HCl (2M) (3500 rpm, 10 min), and then washed and centrifuged with deionized water for multiple times until the pH value of the solution reached 6-7. Then, it was ultrasonically treated in an ice bath under the protection of inert gas, with an ultrasonic power of 200 W and an ultrasonic time of 4 h. After the ultrasonic reaction was completed, it was subjected to high-speed centrifugation (3500 rpm, 30 min), and the upper layer of liquid was poured into a glass culture dish. After freezing in a refrigerator overnight, it was placed in a freeze dryer and freeze-dried for 12 h to obtain few-layer Ti3C2 MXene powder.
[0048] (2) Preparation of Ti3C2 / Ni compacts: Few-layer Ti3C2 MXene was used as a precursor and nano-sized nickel powder was used as a catalyst in a mass ratio of 0.25 g:1.25 g. The mixture was evenly mixed in a glove box and loaded into a 9.5 mm diameter cemented carbide mold. The Ti3C2 / Ni cylindrical blocks were pre-pressed using a powder tablet press. Finally, a six-sided top press was used to apply a compaction stress of 8 GPa to the Ti3C2 / Ni cylindrical blocks and the pressure was maintained for 5 min.
[0049] (3) Chlorine etching of Ti3C2 / Ni compacts: The Ti3C2 / Ni compacts were placed in a tubular furnace, and high-purity argon was introduced at a flow rate of 300 mL / min for 20 minutes. Then, under the protection of the argon atmosphere, the temperature was raised to 1000°C at a rate of 15°C / min. When the temperature in the furnace reached 1000°C, the argon was turned off and chlorine was introduced for etching reaction. The flow rate of chlorine was 60 mL / min, and the etching reaction time was 2.5 hours. After the reaction was completed, the introduction of chlorine was stopped and high-purity argon was introduced. The compacts were cooled to room temperature under the protection of the inert gas argon to obtain a carbon material with a two-dimensional diamond structure.
[0050] (4) Air oxidation purification of 2D diamond: The carbon material sample with a two-dimensional diamond structure obtained by chlorine etching in step 3 was placed in a tube furnace, heated to 525°C at a rate of 5°C / min in an air atmosphere, and maintained at this temperature for 20 hours to remove the non-diamond phase in the sample. As a result, a two-dimensional diamond sub-material with the same structure as in Example 1 was obtained.
[0051] The embodiments of this specific implementation are all preferred embodiments of the present invention, and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made according to the structure, shape, principle, etc. of the present invention should be included in the scope of protection of the present invention. The optional materials of various components are listed in the specification of the present invention, but those skilled in the art should understand that the enumeration of the above-mentioned component materials is not restrictive or exhaustive, and various components can be replaced by other equivalent materials not mentioned in the specification of the present invention, and the purpose of the present invention can still be achieved. The specific embodiments mentioned in the specification are also only for the purpose of explanation, not to limit the scope of the present invention. In addition, the dosage range of each component of the present invention includes any combination of any lower limit and any upper limit mentioned in the specification, and also includes any range formed by the specific content of the component in each specific embodiment as an upper limit or a lower limit combination: all these ranges are included in the scope of the present invention, but only to save space, these combined ranges are not listed one by one in the specification. Each feature of the present invention listed in the specification can be combined with any other feature of the present invention, and this combination is also within the scope of the disclosure of the present invention, but only to save space, these combined ranges are not listed one by one in the specification.
Claims
1. A method for catalytic synthesis of two-dimensional diamond under normal pressure, It is characterized in that The following steps are involved: (1) Take a few layers of Ti 3 C 2 MXene powder and Ni metal powder are mixed evenly and pre-pressed into Ti 3 C 2 / Ni cylindrical block, and then apply compaction stress and maintain it to obtain Ti 3 C 2 / Ni compact; (2) Select the title 3 C 2 The / Ni compact is placed in a tube furnace, argon is introduced for the first time, the temperature is raised, the argon is turned off and chlorine is introduced for etching reaction, and after the reaction is completed, the chlorine is stopped and argon is introduced at the same time to obtain a carbon material with a two-dimensional diamond structure; (3) A carbon material having a two-dimensional diamond structure is placed in a tubular furnace, and the temperature is increased and maintained in an air atmosphere to obtain a two-dimensional diamond.
2. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 1, It is characterized in that The few-layer Ti in step (1) 3 C 2 The preparation method of MXene is: (a) Weigh LiF, add it to HCl solution, and stir at room temperature to obtain a uniform mixed solution; (b) Add Ti to the mixed solution 3 AlC 2 The powder was stirred in a water bath for reaction. After the reaction was completed, it was washed by centrifugation with HCl, and then washed by centrifugation with water several times until the pH value reached 6-7. It was ultrasonically treated in an ice bath under an inert gas atmosphere, centrifuged, and the upper liquid was taken, frozen, and dried to obtain a few-layer Ti 3 C 2 MXene powder.
3. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 2, It is characterized in that The mass volume ratio of LiF to HCl solution in step (a) is (3.2-4):(32-48) g / mL; The concentration of the HCl solution is 9M; The stirring time is 15 to 30 minutes.
4. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 2, It is characterized in that In step (b), Ti 3 AlC 2 The mass ratio of powder to LiF is 1:(1.6-2); The conditions for water bath stirring are: temperature 40-50°C, time 30-36h; The conditions of the HCl centrifugal washing are: a rotation speed of 3200-3800 rpm, a time of 5-10 min, and a centrifugal washing number of 2-3 times; The ultrasonic treatment conditions are: ultrasonic power 160-200W, ultrasonic time 2-4h; The conditions for the water centrifugal washing are: a rotation speed of 3200 to 3800 rpm and a time of 20 to 30 minutes.
5. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 1, It is characterized in that The few-layer Ti in step (1) 3 C 2 The mass ratio of MXene powder to Ni metal powder is 1:1 to 10; The Ti 3 C 2 The number of layers of MXene powder is ≤10; The particle size of the Ni metal powder is 50nm-1μm; The pre-pressing pressure is 2-8 MPa; The applied compaction stress is 5 to 6 GPa and maintained for 5 to 10 minutes.
6. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 1, It is characterized in that The first argon gas introduction in step (2) has a flow rate of 300 to 600 mL / min and a time of 10 to 20 min; The heating conditions are: heating rate 15°C / min, heating to 1000°C; The flow rate of the chlorine gas is 30-60 mL / min; The etching reaction time is 1.5 to 2.5 hours.
7. A method for catalytic synthesis of two-dimensional diamond under normal pressure as claimed in claim 1, It is characterized in that The heating conditions in step (3) are: heating rate 5-10°C / min, heating to 475-525°C; The holding time is 15 to 20 hours.
8. Use of the method according to any one of claims 1 to 7 in synthesizing two-dimensional diamond.
9. A two-dimensional diamond, It is characterized in that It is synthesized by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Ferrite modifying MXene layered gas diffusion electrode as well as preparation method and application thereof
CN108975462A
Method for preparing nano-diamond structure carbon material through normal pressure catalysis
CN110577216A
Nano-diamond structure carbon material prepared under normal pressure in macroscopic quantity as well as preparation method and application of nano-diamond structure carbon material
CN113860285A
Preparation method of diamond composite material
CN114875260A
Process for converting a metal carbide to diamond by etching in halogens
US20010047980A1
